Unsalaried health workers in Sierra Leone: a scoping review of the literature to establish their impact on healthcare delivery - Pieternella Pieterse; Federico Saracini (BMC, 2023)
Abstract Background The World Health Organisation (WHO) estimates a 10 million health worker shortage by 2030. Despite this shortage, some low-income African countries paradoxically struggle with health worker surpluses. Technically, these health workers are needed to meet the minimum health worker-population ratio, but insufficient job opportunities in the public and private sector leaves available health workers unemployed. This results in emigration and un- or underemployment, as few countries have policies or plans in place to absorb this excess capacity. Sierra Leone, Liberia and Guinea have taken a different approach; health authorities and/or public hospitals 'recruit' medical and nursing graduates on an unsalaried basis, promising eventual paid public employment. 50% Sierra Leone's health workforce is currently unsalaried. This scoping review examines the existing evidence on Sierra Leone's unsalaried health workers (UHWs) to establish what impact they have on the equitable delivery of care. Methods A scoping review was conducted using Joanna Briggs Institute guidance. Medline, PubMed, Scopus, Web of Science were searched to identify relevant literature. Grey literature (reports) and Ministry of Health and Sanitation policy documents were also included. Results 36 texts, containing UHW related data, met the inclusion criteria. The findings divide into two categories and nine sub-categories: Charging for care and medicines that should be free; Trust and mistrust; Accountability; Informal provision of care, Private practice and lack of regulation. Over-production of health workers; UHW issues within policy and strategy; Lack of personnel data undermines MoHS planning; Health sector finance. Conclusion Sierra Leone's example demonstrates that UHWs undermine equitable access to healthcare, if they resort to employing a range of coping strategies to survive financially, which some do. Their impact is wide ranging and will undermine Sierra Leone's efforts to achieve Universal Health Coverage if unaddressed. These findings are relevant to other LICs with similar health worker surpluses.